Investigation on Influence of Acetylene Enrichment in Diesel Engines Operating With Microalgae‐Waste Plastic Oil‐Heptane Fuel Mixture - Veeraraghavan Sakthimurugan; Devarajan Yuvarajan; Subbulakshmi Ganesan; Vijay J. Upadhye; Amandeep Gill; Nandagopal kailiappan (Energy Science & Engineering)
ABSTRACT This study investigates the performance and emission characteristics of a diesel engine running on a blend of Scenedesmus obliquus (SO) biodiesel, pyrolyzed waste plastic oil (WP), n‐heptane (H), and acetylene induction (SOPWH), tested under various engine loads at 1500 rpm. The goal is to enhance brake thermal efficiency (BTE) and reduce emissions in alignment with Sustainable Development Goals (SDGs) 7 and 11, which focus on clean energy and sustainable cities. The SO biodiesel was produced via transesterification of algae grown in recycled wastewater, while WP oil was obtained through pyrolysis at 450°C. n‐Heptane was added to optimize the blend, and 4 liters per minute of acetylene was inducted into the intake manifold. Results showed that the SO5WP5H10 blend improved BTE by 0.93% at no load and reduced brake‐specific energy consumption (BSEC) by 0.686 MJ/kW‐h at part load, compared to diesel. Emission reductions included a 28% decrease in hydrocarbon (HC) emissions and a 35% reduction in carbon monoxide (CO) emissions at full load with the SO20WP20H10 blend. Smoke opacity decreased by 19% at maximum load. In terms of combustion, the SO5WP5H10 blend achieved a peak in‐cylinder pressure of 77.5 bar and an efficient mass fraction burnt (MFB), reaching 90% at 25o CA after TDC. Overall, SOPWH blends showed enhanced combustion efficiency and cleaner emissions, positioning them as a sustainable alternative to diesel, without the need for engine modifications. This study aligns with global sustainability goals by offering a cleaner, more efficient fuel option for diesel engines.